Potensi dan Strategi Pengembangan Industri Sasirangan Kota Banjarmasin - Akhsanul Rahmatullah (Ecoplan, 2021)
Banjarmasin has strategic potential in supporting economic growth and has enormous potential to contribute to the Sasirangan Handicraft Industry sub-sector economy. This study aims to: a) analyze the Sasirangan handicraft industry value chain, b) analyze the strategic position of the Sasirangan handicraft industry, c) analyze the empowerment strategy of the Sasirangan handicraft industry in Banjarmasin City. The data used includes primary data obtained through interviews with 40 respondents of Sasirangan artisans in Banjarmasin City. From the research results, the results of the integration of VSA (Value Chain, SWOT, and Analytical Hierarchy Process) are a) The value chain of Sasirangan handicrafts consists of; Suppliers, Manufacturers of Sasirangan Handicraft products, traders, and end consumers. Lack of supply of raw materials for fabrics originating from the island of Java and capital. Meanwhile, the downstream side still lacks support from the Government in product marketing at the national level, b) From the results of the SWOT analysis, this industry is quite strong but faces significant challenges; these results indicate a strategy to improve skills and expertise as well as investment to improve the quality and production capacity to achieve efficiency, c) AHP results obtained marketing strategy to be a priority factor that determines the prospect of Sasirangan Craft. Recommendations from this study include a) Development of the One Village One Product program, in this case, One Sasirangan Village One Product Design, b) Development of the Sasirangan craft industry cluster, c) The government is more communicative regarding financing regulations for artisans, d) Establishing financial institutions and insurance in supporting the capital of MSMEs, e) Involving crafters, creative communities and business people intensively in promotional activities and exhibitions through roadshows, digital marketing, websites and government cooperation.